Effect of contact angle hysteresis on the removal of the sporelings of the green alga Ulva from the fouling-release coatings synthesized from polyolefin polymers - Ucar, Ikrime O.; Cansoy, C. Elif; Erbil, H. Yildirim; Pettitt, Michala E.; Callow, Maureen E.; Callow, James A. (Avs, 2010)
Wettability is one of the surface characteristics that is controlled by the chemical composition and roughness of a surface. A number of investigations have explored the relationship between water contact angle and surface free energy of polymeric coatings with the settlement (attachment) and adhesion strength of various marine organisms. However, the relationship between the contact angle hysteresis and fouling-release property is generally overlooked. In the present work, coatings were prepared by using commercial hydrophobic homopolymer and copolymer polyolefins, which have nearly the same surface free energy. The effects of contact angle hysteresis, wetting hysteresis, and surface free energy on the fouling-release properties for sporelings of the green alga Ulva from substrates were then examined quantitatively under a defined shear stress in a water channel. The ease of removal of sporelings under shear stress from the polymer surfaces was in the order of PP>HDPE>PPPE>EVA-12 and strongly and positively correlated with contact angle and wetting hysteresis; i.e., the higher the hysteresis, the greater the removal. (C) 2010 American Vacuum Society. [DOI: 10.1116/1.3483467]
Keywords: Engineered Antifouling Microtopographies; Ethylene-Vinyl Acetate; Surface-Free Energy; Tropical Sea Stars; Superhydrophobic Surface; Enteromorpha-Linza; Adhesion Strength; Sessile Drops; Attachment; Roughness